2022
DOI: 10.1101/2022.01.27.477154
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptomic and phenomic investigations reveal elements in biofilm repression and formation in the cyanobacteriumSynechococcus elongatusPCC 7942

Abstract: Biofilm formation by photosynthetic organisms is a complex behavior that serves multiple functions in the environment. Biofilm formation in the unicellular cyanobacterium Synechococcus elongatus PCC 7942 is regulated in part by a set of small secreted proteins that promotes biofilm formation and a self-suppression mechanism that prevents their expression. Little is known about the regulatory and structural components of the biofilms in PCC 7942, or response to the suppressor signal(s). We performed transcripto… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…A genetic screen using a barcoded transposon library suggested that inactivation of gene Synpcc7942_0051 causes biofilm development (Simkovsky et al, 2022). Briefly, this S. elongatus library of mutants was grown, a biofilm was allowed to form, and DNA extracted from the biofilm was analysed by high-throughput sequencing.…”
Section: Inactivation Of Synpcc7942_0051 Results In Biofilm Formationmentioning
confidence: 99%
See 3 more Smart Citations
“…A genetic screen using a barcoded transposon library suggested that inactivation of gene Synpcc7942_0051 causes biofilm development (Simkovsky et al, 2022). Briefly, this S. elongatus library of mutants was grown, a biofilm was allowed to form, and DNA extracted from the biofilm was analysed by high-throughput sequencing.…”
Section: Inactivation Of Synpcc7942_0051 Results In Biofilm Formationmentioning
confidence: 99%
“…A genetic screen using a barcoded transposon library suggested that inactivation of gene Synpcc7942_0051 causes biofilm development (Simkovsky et al ., 2022 ). Briefly, this S .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations